2009
DOI: 10.1088/0953-8984/21/19/195501
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Mössbauer isomer shifts from first principles

Abstract: Computation of the observables of a Mössbauer spectrum, primarily the isomer shift, from a first-principles approach is described. The framework used is density functional theory using the projector augmented wave formalism (DFT PAW), which enables efficient computation even of many-electron solids such as SnCl(2). The proper PAW version of the isomer shift is derived and shown to be correct through comparison of computed shifts and experiment in a variety of compounds based on tin, germanium and zinc. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Total contact densities also match well (e.g., DHF, 188,242 e -/a 0 3 ; DFT-PAW, ∼188,000 e -/a 0 3 for Sn 4+ ). Tests with point-nucleus DFT-PAW models show much more variable contact densities (∼1.6 × DHF) and much higher absolute contact densities (>400,000 e -/a 0 3 ) (28). DHF model contact densities increase by less than 2% if a much larger "quadruple-ζ" basis set is used.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Total contact densities also match well (e.g., DHF, 188,242 e -/a 0 3 ; DFT-PAW, ∼188,000 e -/a 0 3 for Sn 4+ ). Tests with point-nucleus DFT-PAW models show much more variable contact densities (∼1.6 × DHF) and much higher absolute contact densities (>400,000 e -/a 0 3 ) (28). DHF model contact densities increase by less than 2% if a much larger "quadruple-ζ" basis set is used.…”
Section: Methodsmentioning
confidence: 98%
“…The mean-squared radius difference found in ref. 28, 0.0048 fm 2 , is smaller mainly because of the use of point-nucleus PAW datasets. Using the calculated sensitivities in Table 2, energy shifts and 124 Sn/ 116 Sn fractionation factors have been estimated for a suite of tin sulfide crystals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There remains the question of whether even all-electron accuracy in the valence space is sufficient for accurate representation of observables close to the nuclei, where conventional wisdom would suggest that deep core polarizations might be quite significant for properties such as the electric field gradient or Fermi contact interaction. Such concerns turn out to be unwarranted, however, as our experience and others have shown that the PAW formalism together with a typical chemical valence/core separation are sufficient for accurate description of nuclear point properties such as the electric field gradient [54][55][56], Fermi contact interaction [57] and magnetic chemical shielding [58].…”
Section: Properties At the Nuclei: Electric Field Gradients And Mössbmentioning
confidence: 99%